1997
DOI: 10.1021/bi971026e
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofolate Reductase Protein Inhibits Its Own Translation by Binding to Dihydrofolate Reductase mRNA Sequences within the Coding Region

Abstract: Previous studies suggest that dihydrofolate reductase (DHFR) regulates its own translation. Moreover, intracellular levels of DHFR protein increase following exposure to the antifolate methotrexate (MTX), suggesting that MTX may release the translational inhibition mediated by DHFR [Chu et al. (1993) Biochemistry 32,4756-4760; Ercikan et al. (1993) Adv. Exp. Med. Biol. 338, 537-540]. To further investigate the role of DHFR in translational autoregulation, we have considered the possibility that DHFR directly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 23 publications
2
71
3
Order By: Relevance
“…Notably, we demonstrate that this mechanism can be utilized for regulation of transgene expression when transgenes are located in a 3Ј cis arrangement with DHFR FS . By codon-optimizing DHFR FS to remove the mRNA binding sequence previously identified (15,16), we find that MTX continues to induce an increase in DHFR FS expression independent of the mRNA sequence and that the addition of TYMS SS unexpectedly blunts this increase. This finding suggests a novel method of post-transcriptional DHFR expression that is regulated by the enzymatic action of TYMS SS .…”
Section: Methotrexate (Mtx) Is An Anti-folate That Inhibits De Novo Pmentioning
confidence: 83%
See 2 more Smart Citations
“…Notably, we demonstrate that this mechanism can be utilized for regulation of transgene expression when transgenes are located in a 3Ј cis arrangement with DHFR FS . By codon-optimizing DHFR FS to remove the mRNA binding sequence previously identified (15,16), we find that MTX continues to induce an increase in DHFR FS expression independent of the mRNA sequence and that the addition of TYMS SS unexpectedly blunts this increase. This finding suggests a novel method of post-transcriptional DHFR expression that is regulated by the enzymatic action of TYMS SS .…”
Section: Methotrexate (Mtx) Is An Anti-folate That Inhibits De Novo Pmentioning
confidence: 83%
“…This construct is referred to as FLAG-DHFR FS -2A-eGFP pSBSO (D FS G). The DHFR FS was also codon-optimized to remove the original codon sequence, with specific attention paid to the coding region where DHFR is known to bind its own mRNA (15,16 . A selection-free RFP plasmid NLS-mCherry pSBSO (RFP) was utilized as a control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first glance, it appears unusual that the coding region of an mRNA is the target of a translational regulatory mechanism; however, genome-wide analyses of interactions of regulatory RNA-binding proteins with mRNAs have revealed surprisingly large numbers of interactions that take place in the coding regions of the cognate mRNAs (Hogan et al, 2008;Hafner et al, 2010). Previous studies have also identified specific regulatory proteins that bind to the coding regions of certain mRNAs, such as the thymidylate synthase and dihydrofolate reductase, both of which bind to the coding regions of their own mRNAs (Ercikan-Abali et al, 1997;Lin et al, 2000;Zhang et al, 2010) and the RNA-binding protein HuR, which interacts with the coding region of CD83 RNA (Prechtel et al, 2006). Target sites for microRNAs are also not restricted to the 3 0 -UTRs but can occur in the coding region of certain mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to a phenomenon in which the DHFR message binds to DHFR, thus regulating its availability for translation. In the presence of an antifolate, the message is released, translation is enhanced, and synthesis of protein is increased (Chu et al, 1993;Ercikan et al, 1993;Ercikan-Abali et al, 1997;Schmitz et al, 2001). Regulation of DHFR expression by this mechanism was absent in the malaria parasite and suggested as a factor in the utility of antifolates in the treatment of this disease (Zhang and Rathod, 2002).…”
Section: Alterations In Dhfrmentioning
confidence: 99%